2017
DOI: 10.1093/scan/nsx021
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the development of emotion circuitry in adolescents at risk for substance abuse: a longitudinal fMRI study

Abstract: There is substantial evidence for behavioral sex differences in risk trajectories for alcohol and substance use, with internalizing factors such as negative affectivity contributing more to female risk. Because the neural development of emotion circuitry varies between males and females across adolescence, it represents a potential mechanism by which underlying neurobiology contributes to risk for substance use. Longitudinal functional magnetic resonance imaging was conducted in males and females (n = 18 each)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 118 publications
(120 reference statements)
4
22
0
Order By: Relevance
“…In this study, it was demonstrated that the alcohol pictures induced a stronger urge to drink in men compared to women, whereas women reported a stronger positive valence towards the nonalcoholic pictures, which could partly explain the reported sex differences in neural cue-reactivity. Moreover, the current findings also support the hypothesis that substance use and relapse in men is predominantly driven by external substance-related cues (positive reinforcement), whereas substance use and relapse in women is driven predominantly by internal negative emotional states (negative reinforcement) (Cosgrove et al, 2014;Hardee et al, 2017). In line with this, animal research demonstrated that corticosterone treatment, which is consistent with a mild physiological stressor, only induced alcohol-reinstatement in female but not in male rats (Bertholomey, Nagarajan, & Torregrossa, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, it was demonstrated that the alcohol pictures induced a stronger urge to drink in men compared to women, whereas women reported a stronger positive valence towards the nonalcoholic pictures, which could partly explain the reported sex differences in neural cue-reactivity. Moreover, the current findings also support the hypothesis that substance use and relapse in men is predominantly driven by external substance-related cues (positive reinforcement), whereas substance use and relapse in women is driven predominantly by internal negative emotional states (negative reinforcement) (Cosgrove et al, 2014;Hardee et al, 2017). In line with this, animal research demonstrated that corticosterone treatment, which is consistent with a mild physiological stressor, only induced alcohol-reinstatement in female but not in male rats (Bertholomey, Nagarajan, & Torregrossa, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…decreased in males, increased in females). As sex-dependent differences in amygdala activation also emerge during adolescence, 59 , 60 divergence in thermal sensitivity between males and females may be clearer in early adulthood than at younger ages. Alterations in socio-emotional circuits, which are influenced by biological vulnerability, early life adversity, and parenting, have been proposed as a link between preterm birth and subsequent psychosocial and emotional outcomes, 56 and we suggest extending this model to include effects on experimental pain sensitivity in EP young adults.…”
Section: Discussionmentioning
confidence: 99%
“…As cognitive reappraisal engages a wide network of brain regions (Kohn et al, 2014;Messina et al, 2015;Wager, Davidson, Hughes, Lindquist, & Ochsner, 2008), the present results suggest that anxiety and depression are negatively associated with deficiencies recruiting a broader neural network. These regions are hypothesized to govern the behavioral output of reappraisal, as the SMA integrates input from frontal regions responsible for the formation of an internal representation of regulation goals with a behavioral response (Etkin et al, 2015), and the precentral gyrus governs internal emotional experiences that help guide motoric output (Hardee et al, 2017). These regions are hypothesized to govern the behavioral output of reappraisal, as the SMA integrates input from frontal regions responsible for the formation of an internal representation of regulation goals with a behavioral response (Etkin et al, 2015), and the precentral gyrus governs internal emotional experiences that help guide motoric output (Hardee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, prior work confirms involvement of the SMA (Etkin, Büchel, & Gross, 2015;Kohn et al, 2014;Wager et al, 2008) and precentral gyrus (Picó-Pérez, Radua, Steward, Menchón, & Soriano-Mas, 2017) during reappraisal. These regions are hypothesized to govern the behavioral output of reappraisal, as the SMA integrates input from frontal regions responsible for the formation of an internal representation of regulation goals with a behavioral response (Etkin et al, 2015), and the precentral gyrus governs internal emotional experiences that help guide motoric output (Hardee et al, 2017). Although involvement of the cuneus during reappraisal is not well documented, this region is implicated in visual processing (Parker, Zalusky, & Kirbas, 2014).…”
Section: Discussionmentioning
confidence: 99%